EMI in a postgraduate logistics course: possibilities and directions - Matochi, Isabela Nepomuceno; Kobayashi, Eliana (The ESPecialist, 2025)
English Medium Instruction (EMI) is one of the many internationalisation initiatives promoted by higher education institutions to better prepare students for the job market and raise the university's profile. This qualitative investigation analyzes through questionnaires the opinions and perceptions on EMI implementation of professors and coordinator of a postgraduate course in Logistics. Despite the fact that 70% of the participants classified EMI as a very important internationalization action, their English proficiency level may become an obstacle to such implementation since it varies from A2 to C1 levels of the Common European Framework of Reference (CEFR) in some skills. In addition, the results reveal that students’ English level might also be an issue for EMI.